Embryonic nervous system genes predominate in searches for dinucleotide simple sequence repeats flanked by conserved sequences - Riley, Donald E. (2008)
To study evolution of dinucleotide simple sequence repeats (diSSRs) we searched recently available mammalian genomes for UTR-localized diSSRs with conserved upstream flanking sequences (CFS). There were 252 reported Homo sapiens genes containing the repeats (AC)n, (GT)n, (AG)n or (CT)n in their UTRs including 22 (8.7%) with diSSR-upstream flanking sequences conserved comparing divergent mammalian lineages represented by Homo sapiens and the marsupial, Monodelphis domestica. Of these 22 genes, 19 had known functions including 18 (95%) that proved critical for mammalian nervous systems (Fishers exact test, P < 0.0001). The remaining gene, Cd2ap, proved critical for development of kidney podocytes, cells that have multiple similarities to neurons. Gene functions included voltage and chloride channels, synapse-associated proteins, neurotransmitter receptors, axon and dendrite pathfinders, a NeuroD potentiator and other neuronal activities. Repeat length polymorphism was confirmed for 68% of CFS diSSRs even though these repeats were nestled among highly conserved sequences. This finding supports a hypothesis that SSR polymorphism has functional implications. A parallel study was performed on the self-complementary diSSRs (AT)n and (GC)n. When flanked by conserved sequences, the self-complementary diSSR (AT)n was also associated with genes expressed in the developing nervous system. Our findings implicate functional roles for diSSRs in nervous system development.